Delineation and characterisation of the Takula watershed in Kumaon Himalayas for soil and water conservation - NAGDEV, RITU; MAHAPATRA, S. K.; YADAV, R. P.; SINGH, S K. (Journal of Soil and Water Conservation, 2020)
Takula watershed in Almora district of Kumaon Himalayas in Uttarakhand was delineated and characterised using remote sensing and GIS techniques. On the basis of image interpretation and ground truth studies, major physiographies identified are escarpments, ridge tops, side slopes and fluvial valleys. They were further sub-divided into eight physiographic units based on slope gradient and length. Escarpments occur on very steep slopes and are covered with barren rocky land associated with rock outcrops. Seven soils (Takula 1 to 7) were identified in other three physiographies of the watershed, mapped into 14 soil mapping units and soil map was generated. Soils of ridge tops (Takula 1 and 2) occur on moderately steep to steep slopes and are shallow to moderately shallow, excessively drained, gravelly sandy loam to gravelly loam, brown to dark yellowish brown in colour and strongly acidic (pH 5.04 to 5.34) in reaction. They are developed on mica schist/ quartzite/slate having A-AC-C horizons and classified as loamy skeletal Lithic/Typic Udorthents. They are evaluated as class IV land under land capability classification. Soils of side slopes (Takula 3 to 6) occur on moderate to very steep slopes and are very shallow to moderately deep, somewhat excessive to excessively drained, gravelly sandy loam, gravelly loam and loamy sand in texture, brown to yellowish brown in colour and moderately to strongly acidic (pH 5.17 to 5.90) in reaction. They are developed on mica schist/slate and have A-AC-C horizons, being classified as loamy skeletal, coarse/fine loamy Lithic/Typic Udorthents and Typic Udipsamments. They are evaluated as class III, IV, V and VI lands. Soils of fluvial valleys (Takula 7) occur on gentle slopes and are very deep, well drained, sandy loam, brown to dark yellowish brown in colour and slightly acidic (pH 6.15 to 6.40) in reaction. They are developed on alluvium/colluvium and have A-B-C horizons, being classified as coarse loamy, Dystric Eutrudepts. They are assessed as land capability class III. The study area is highly prone to degradation due to sloppy landscape, deforestation, over grazing, indiscriminate human interventions, etc. Major constraints are limited soil depth, gravelliness, severe to very severe erosion and low nutrient retention capacity. Hence, proper soil and water conservation measures should be adopted to arrest further degradations, maintain soil health and enhance productivity.